Suplementasi Ekstrak Kasar Bonggol Nanas (Ananas comosus L) dan Batang Pisang (Musa sp.) Pada Pemeliharaan Benih Ikan Lele (Clarias sp.) di Kolam Tanah Gambut - Djauhari, Ricky; Christiana, Ivone; Yulintine, Yulintine; Maryani, Maryani; Monalisa, Shinta Sylvia; Gunawan, Irawadi; Marcelina Naibaho, Sophia Gabriela (Universitas Batangahari Jambi, 2024)
One of the obstacles in cultivating catfish (Clarias sp.) is its low feed efficiency. Therefore, a breakthrough innovation is needed in catfish cultivation to increase the efficiency of feed utilization which will lead to increase the production and profits in catfish cultivation businesses. This study aimed to evaluate the effect of supplementation of pineapple and banana stem crude extract on the growth performance of catfish in flooded peat ponds. In this study, pineapple and banana stem crude extract was mixed into the feed at doses of 0 (A), pineappleÂ stem crude extract 6% (B), banana stem crude extract 2% (C), and combination pineapple 6% and banana stem crude extract 2% (D) with three repetitions. Fish with an initial weight of 1.25 g were randomly stocked in 12 nets sizing 1 x 1 x 1 m3 installed in earthen ponds at a density of 40 fish/net. Fish were given the experimental feed to apparent satiation twice a day for 14 days. Supplementation combination of pineapple at a dose of 6% and banana stem crude extract at a dose of 2% (treatment D) showed better results on catfish growth performance compared to other treatments. Supplementation combination of pineapple and banana stem crude extract showed a positive effect on feed consumption efficiency (160 g), feed utilization efficiency (100,4%) as indicated by the feed conversion ratio value (1.05) which was lower than other treatments. Supplementation of pineapple stem crude extract can be a new breakthrough innovation in the fish cultivation in peat ponds considering its significant role in reducing oxidative stress during fish cultivation